Gay and bisexual men engage in fewer risky sexual behaviors while traveling internationally: a cross-sectional study in San Francisco. (29th October 2014) - Truong, Hong-Ha M; Fatch, Robin; Grasso, Michael; Robertson, Tyler; Tao, Luke; Chen, Yea-Hung; Curotto, Alberto; McFarland, Willi; Grant, Robert M; Reznick, Olga; Raymond, H Fisher; Steward, Wayne T
Abstract : Background: International travel poses potential challenges to HIV prevention. A number of studies have observed an association between travel and behavioural disinhibition. In the present study, we assessed differences in sexual behaviour while travelling internationally and within the USA, compared with being in the home environment. Methods: A probability-based sample of men who have sex with men (MSM) from the San Francisco Bay Area who had travelled internationally in the previous 12 months was recruited through an adapted respondent-driven sampling methodology (N=501). Participants completed interviewer-administered, computer-assisted surveys. Results: Detailed partner-by-partner behavioural data by destination type were collected on 2925 sexual partnerships: 1028 while travelling internationally, 665 while travelling within the USA and 1232 while staying in the San Francisco Bay Area. The proportion of partnerships during international travel that involved unprotected anal intercourse (UAI) was lower compared with during domestic travel and staying locally. International travel was associated with decreased odds of receptive UAI (AOR=0.65, p=0.02) compared with staying locally and there was a trend towards decreased odds of insertive UAI (AOR=0.70, p=0.07). Conclusions: MSM engaged in proportionately fewer sexual activities which present a high HIV transmission risk when travelling internationally, namely unprotected receptive and insertive anal intercourse and particularly with HIV serodiscordant partners. The lower sexual risk-taking during international travel was robust to controlling for many factors, including self-reported HIV serostatus, age, relationship status and type of partnership. These findings suggest that when travelling internationally, MSM may experience behavioural disinhibition to a lesser extent than had been described previously.